Peranan Silaturahim Dalam Komunikasi Bisnis Pada Kesuksesan Pengusaha Batik Jetis Sidoarjo - Chisty, Althaf Aulia; Faiza, Siti Inayatul (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to identify and explain how gathering in business communication that occurs in batik entrepreneurs at Jetis, Sidoarjo are able to play a role in achieving entrepreneurial success. This theme will be the basic reason for explaining the role of gathering in business communication on batik entrepreneurs success that has been achieved at Jetis, Sidoarjo. The gathering is conducted between businessmen in local scope and outside of Sidoarjo, and the craftsmen and other employees.This study used a qualitative approach with descriptive methods. Data was collected through documentation, interviews, and direct observation to study the object. To test the validity of data, this study uses three triangulations such as triangulation of sources, theories, and methods.The research result showed that gathering in business communication conducted by batik entrepreneurs at Jetis, Sidoarjo, intended for the survival and success in batik entrepreneurship, as well as in the context of observance. Implementation gathering conducted in jetis, Sidoarjos batik entrepreneurship is the formation of batik association in Sidoarjo, beside that gathering also help the entrepreneurs to made business collaborations between other batik entrepreneurs and create working atmosphere of kinship. It helps the entrepreneur to developing their business and achieve success.